Ex-ante cost-benefit analysis of high-end and low-cost Wireless Sensor Network (WSN) technology packages for efficient irrigation water management in the Philippines - Aringo, Marielle Q.; Ella, Victor B.; Martinez, Camille G.; Pereira, Gamiello S. (2022)
Four wireless sensor network (WSN) technology packages developed for efficient irrigation water management in the Philippines were subjected to ex-ante cost-benefit analysis (CBA) to assess their financial viability. The WSN technologies include high-end and low-cost wireless sensors for upland crop production with drip irrigation system and lowland crop production with alternate wetting and drying (AWD). Results showed that the high-end WSN technology packages are only viable for high-value crops such as red onion, bell pepper, and hot pepper. The low-cost WSN technology packages are viable for all selected crops except sweet corn. Minimum areas were also generated for each crop for the technology packages to be viable. Sensitivity analysis showed that the viability of the technologies generally declines at higher discount rates but can be improved by reducing the investment cost and increasing the cropping intensity and crop production area.
Keywords: Wireless Sensor Network (WSN) technology; Irrigation water